Floristic diversity of dipterocarpaceae in the Sungai Harapan Protected Forest, Batam Island, Indonesia - Enny Insusanty; Muhammad Hisyam; Azwin; Sri Rahayu Prastyaningsih (Talenta Publisher, 2026)
The Dipterocarpaceae family plays an important role as a dominant component of lowland tropical rainforest ecosystems, particularly within the Sunda Shelf region, such as Batam Island, Indonesia. However, these species are increasingly threatened by anthropogenic activities, including deforestation and land-use conversion, underscoring the need for conservation efforts supported by scientific data. This study aimed to identify species of the Dipterocarpaceae family, analyze the Important Value Index (IVI), and determine species diversity and evenness. The research was conducted using an exploratory survey method with Systematic Sampling with Random Start across an area of 1.74 ha within the 87 ha Special Block Protected Forest. Primary data were collected from different growth stages, including seedlings, saplings, poles, and trees, along with measurements of temperature and humidity. Data were analyzed qualitatively and quantitatively using the IVI, Shannon–Wiener diversity index, and evenness index. The results recorded 20 species across 6 genera (Cotylelobium, Dipterocarpus, Dryobalanops, Hopea, Shorea, and Vatica) from 44 plots, totaling 590 individuals. The number of individuals consisted of 228 seedlings, 172 saplings, 77 poles, and 113 trees. The highest IVI values were observed in Hopea beccariana Burck at the seedling (52.40%) and sapling (55.40%) stages, while Shorea curtisii Dyer ex King ssp. S. curtisii dominated the pole (103.68%) and tree (93.06%) stages. Shannon–Wiener diversity index values ranged from 1.81 to 2.05, indicating moderate diversity across all growth stages. Evenness index values ranged from 0.67 to 0.86, indicating high species evenness